Optimal protein extraction methods from diverse sample types for protein profiling by using Two-Dimensional Electrophoresis (2DE) - Tan, A.A.; Azman, S.N.; Abdul Rani, N.R.; Kua, B.C.; Sasidharan, S.; Kiew, L.V.; Othman, N.; Noordin, R.; Chen, Y. (2011)
There is a great diversity of protein samples types and origins, therefore the optimal procedure for each sample type must be determined empirically. In order to obtain a reproducible and complete sample presentation which view as many proteins as possible on the desired 2DE gel, it is critical to perform additional sample preparation steps to improve the quality of the final results, yet without selectively losing the proteins. To address this, we developed a general method that is suitable for diverse sample types based on phenolchloroform extraction method (represented by TRI reagent). This method was found to yield good results when used to analyze human breast cancer cell line (MCF-7), Vibrio cholerae, Cryptocaryon irritans cyst and liver abscess fat tissue. These types represent cell line, bacteria, parasite cyst and pus respectively. For each type of samples, several attempts were made to methodically compare protein isolation methods using TRI-reagent Kit, EasyBlue Kit, PRO-PREP TM Protein Extraction Solution and lysis buffer. The most useful protocol allows the extraction and separation of a wide diversity of protein samples that is reproducible among repeated experiments. Our results demonstrated that the modified TRI-reagent Kit had the highest protein yield as well as the greatest number of total proteins spots count for all type of samples. Distinctive differences in spot patterns were also observed in the 2DE gel of different extraction methods used for each type of sample.